Information Technology Work Value Differences - Toskin, Katarzyna; McCarthy, Richard V. (Journal of Computer Information Systems, 2021)
This study investigates reasons behind high employee turnover of IT professionals through the value placed on intrinsic, extrinsic, leisure, and social rewards. It addresses two questions; what are the most preferred work values by IT professionals, and how do they differ from other professions. Data was collected via a survey using subjects from Amazon Mechanical Turk. A sample of 380 respondents was used. Key findings reveal that intrinsic rewards were the most important work values for IT professionals followed by leisure, extrinsic, and social rewards. Furthermore, when compared to the preferences of non-IT professionals, the levels of preferences for intrinsic rewards were statistically significantly higher for IT professionals than all other professions. This study provides valuable insight regarding key motivating factors of IT professionals and offers practical implications for practitioners relating to job characteristics that are most likely to reduce IT turnover and rethink their rewards systems.
_eprint: https://doi.org/10.1080/08874417.2019.1639567
Keywords: IT employee motivation; Information technology; dept.bis; peer-reviewed; turnover; work values

Flow through Regression: A Guide to Interpreting and Communicating Regression Models for Data Analytics Students - Toskin, Katarzyna; Kunene, Niki (Information Systems Education Journal, 2021)
Faculty teaching data analytics at undergraduate level are often faced with the tension created by student under-preparedness, the demands of the course, and time constraints. How do faculty close this gap? In this paper, we propose the use of flow diagramming as an accessible method for interpreting regression analyses, in ways that are time efficient and not alienating to the student. Our study shows that the use of such flow diagrams has a positive effect on student understanding without additional remedial instruction. Time saved can be directed at core learning objectives of the analytics.
ERIC Number: EJ1319909
Keywords: Business Administration Education; College Faculty; College Preparation; Data Analysis; Pretests Posttests; Remedial Instruction; Statistics Education; Teaching Methods; Time Management; Undergraduate Students; Visual Aids; dept.bis; peer-reviewed; ⛔ No DOI found

Emotional and Cultural Intelligences' Impact on Extra-Role Job Performance in Russia - Engle, R. L; Dimitriadi, N.; Toskin, K (International Business: Research, Teaching, and Practice, 2021)
Keywords: dept.bis; ⛔ No DOI found

The Unintentional Risk or Liability of Implementing Deploying, or Adopting a Private Blockchain Network - Pisano, Mark; Bassett, Richard (ACET Journal of Computer Education and Research, 2021)
Keywords: dept.bis; peer-reviewed; ⛔ No DOI found

Organizational Cost and Complexity Saving Opportunities via the Development, Deployment, and Implementation of Blockchain Networks - Pisano, Mark; Bassett, Richard (Information Technology and Management Science, 2021)
Blockchain is being promoted as the platform to disrupt business as usual in many transaction-heavy sectors. Questions remain about the future standards of blockchain, their feature set, functionality, and the willingness of organisations to disrupt their existing revenue streams via blockchain. The most significant near-term promise that affords industry is the cost and complexity savings via the standardization of their technology infrastructure stacks. This paper explores the benefits available of reduced costs and complexity via the adoption of blockchain.
Number: 1
Keywords: Blockchain; banking; deployment; dept.bis; human capital; industries; peer-reviewed

An economic model of machine translation - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2021)
1 citations (Crossref) [2023-10-31]
Keywords: dept.bis; peer-reviewed